The Contribution of Some Production and Reproduction Traits to the Variation in Holstein-Friesian Female Birth Weights - Kharoofa, A.D.S; Salhab, S.A.; Ahmed, M-K.A.; Zaied, A.A. (Al-Mukhtar Journal of Sciences, 1997)
The path analysis method was applied to 1023 Holstein-Friesian records. The aim was to study the effect of the following causal variables: parity, open period, dry period, gestation period, lactation length, and total production on the variation in female birth weight (as a dependent variable). The results showed that gestation period was the major contributor to the variation in female birth weight (9.14%). followed by the previous lactation (7.5%), and the open period (5.84%). The combined effect of the variables studied was negative. This led to a reduction in the sum of the individual effects. They amounted to 13.94% of the total variation in birth weights. The direct effects were negative for lactation length (-0.2739), and positive for gestation period and the open period. The total of the indirect effects was positive for lactation lenght (0.3342) and negative for the open period (-0.1672). Consequently, the overall effects of these two variables were small. The Total effect of gestation period (0.3215) and parity (0.2056) was significant (P<0.01) and positive. It was also significant (P<0.05) for total production (0.1483).